Козацька система "Спас" на Миколаївщині - Котляр, Ю. (Чорноморська минувшина, 2013)
У статті на основі на джерельного матеріалу авторів методик практичного вивчення «Спасу» розглядаються духовні основи цього явища. Серед дієвих міфологічних систем, які є характерними для українського етносу та які були прийняті козацтвом, необхідно виділити систему, під назвою «Спас», яка є своєрідним інструментом для пізнання енергетичних можливостей людини. Презентовано прояви системи «Спас» на Миколаївщині, де її хранителями виступають представники родів козаків- характерників Скульських і Топор. In the article on basis on a spring, material of authors of methods of practical study wills «Spas» spiritual bases of this phenomenon are examined. The displays of the system «Spas» are rotined on Mykolaiv. Among the mythological systems, that are characteristic for the Ukrainian ethnos and which were adopted by the Cossacks, one should pick out the system called «Spas». According to the definition given by A. Skulskiy, the founder of «Spas» of the Black Sea region, «Spas» is a system of trance culture of the Ukrainian people. The purpose of the article, which is based on the works of the authors of methods of practical «Spas» study as: Anatoliy Maksimovich Skulskiy, Vasiliy Andriovich Chumachenko and Victor Myhaylovich Chernikov (Topor) is to find out the origin of the «Spas» system and define its role in the spiritual revival of the personality. В статье на основе источников авторов методик практического изучения «Спаса» рассматриваются духовные основы этого явления. Показаны проявления системы «Спас» на Николаевщине. Среди действенных мифологических систем, которые являются характерными для украинского этноса и которые были приняты казачеством, необходимо выделить систему, под названием «Спас». Согласно определению, A. Скульского, основателя «Спаса Причерноморья», «Спас» – это система трансовой культуры украинского народа.